Outsourcing a sales task, not the entire function : outcome determinants - Riepponen, Taina (2019)
Outsourcing a sales task instead of an entire sales function has gained popularity among companies operating in B2B markets. Sales operates right in the customer interface which makes it a critical business function to outsource. However, prospecting as a sales task requires little firm related expertise and more technological related one, which makes it attractive to firms to outsource. Current research in outsourcing outcome determinants has a considerable gap in terms of a timely phenomenon of a sales task outsourcing. This study utilizes a framework, created by Lacity et al. (2016), that concerns outsourcing outcome determinants when outsourcing an entire business function and expands the current knowledge by exploring such outsourcing outcome determinants in prospecting outsourcing. Further, the study explores possible risks in prospecting outsourcing and ways to avoid such. The study was conducted as a qualitative single case study for which eight client-side informants and two provider-side experts were interviewed. The main findings of the study emphasize the importance of communication, client understanding, and trust when aiming for successful prospecting outsourcing. A significant amount of the findings are parallel to the current knowledge in business function outsourcing. However, the study also revealsfourdeterminantsthat are new to prior research and seem to affect prospecting outsourcing success: customer understanding, proactivity, a client-specific communication, and provider-specific communication.